Profit raising entry effects in network industries with Corporate Social Responsibility - Fanti, Luciano; Buccella, Domenico (Economics and Business Letters, 2017)
This note investigates the possibility of profit raising entry in network industries where firms follow Corporate Social Responsibility (CSR) behaviours, showing the interaction between the network and CSR features. In particular, for high levels of the network effect, an incumbent’s profits raising entry effect occurs. The latter result is at odds with the conventional wisdom and shows another channel the preceding literature has so far not explored for the possibility of a profit raising entry.